2006
DOI: 10.1101/gad.1410506
|View full text |Cite
|
Sign up to set email alerts
|

Post-transcriptional small RNA pathways in plants: mechanisms and regulations

Abstract: For a long period of time, DNA, the support of heredity, and proteins, the actors of the cellular machinery, have been considered the most important components of biological systems. By contrast, RNA was originally considered as an intermediate molecule, bridging the gap between DNA and protein (mRNA), or serving functional roles during splicing (snRNA) and translation (tRNA and rRNA). The recent discovery of an increasing number of large and small non-protein-coding RNAs with specific regulatory roles has cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
513
0
14

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 670 publications
(533 citation statements)
references
References 107 publications
(208 reference statements)
6
513
0
14
Order By: Relevance
“…mRNA cleavage in RISC is directed by short interfering RNAs (siRNAs) that derive from the processing of long dsRNAs that are complementary to target mRNAs by the RNase III Dicer. Mechanistically, PTGS is very similar to mRNA cleavage directed by endogenous miRNAs and trans-acting siRNAs (Vaucheret 2006).…”
Section: Introductionmentioning
confidence: 99%
“…mRNA cleavage in RISC is directed by short interfering RNAs (siRNAs) that derive from the processing of long dsRNAs that are complementary to target mRNAs by the RNase III Dicer. Mechanistically, PTGS is very similar to mRNA cleavage directed by endogenous miRNAs and trans-acting siRNAs (Vaucheret 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to miRNAs that are derived from single-stranded precursors, siRNAs are generated by Dicer-like proteins from long doublestranded RNAs. Several types of endogenous siRNAs have been found in Arabidopsis, such as trans-acting siRNAs, nat-siRNAs, and heterochromatic siRNAs (reviewed in Brodersen and Voinnet, 2006;Vaucheret, 2006). In addition to the endogenous siRNAs, viruses and transgenes also give rise to siRNAs (reviewed in Brodersen and Voinnet, 2006;Vaucheret, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs are mainly bound by AGO1, and ta-siRNAs are bound by AGO6 and AGO2, whereas most of the 24 nt small RNAs are directed to AGO4 and AGO5 [5,[17][18][19]. During the process of sorting certain classes of small RNAs into their corresponding AGOs, the 5′ terminal nucleotide of the small RNAs plays a significant role, as it was recently reported that different AGOs have a strong bias for a distinct 5′ terminal nucleotide: U for AGO1, A for AGO2, A for AGO4, and C for AGO5 [19,20].…”
Section: Introduction To Small Rnas In Plantsmentioning
confidence: 99%
“…Plant sRNAs may also be categorized as miRNAs or siRNAs based on their origin: miRNAs are derived from imperfectly matched stem-loop structures that are formed from single-stranded RNA (ssRNA) precursors, whereas siRNAs are derived from perfectly-or nearly perfectlymatched double-stranded RNAs (dsRNAs) produced by the activity of RNA-dependent RNA polymerases (with genes named as "RDR1," "RDR2," etc.) or from ssRNA transcripts including inverted repeats that fold back to form a dsRNA region [4,5]. The larger class of siRNAs can be further subdivided into categories including trans-acting siRNAs (ta-siRNAs), natural cis-antisense transcript derived siRNAs (nat-siRNAs) and heterochromatic siRNAs (hc-siRNAs).…”
Section: Introduction To Small Rnas In Plantsmentioning
confidence: 99%
See 1 more Smart Citation